One-year activity of a "Casa de Espera" (Maternity Waiting Home) in the south of Angola. (13th November 2019) - Fattorini, M; Raguzzoni, G; Cuccaro, C; Nante, N; Messina, G; Ndilimondjo, J M N; Ndapandula, W; Tuitileni, G; Caresia, C; Putoto, G
Abstract: Background: Maternity Waiting Homes (MWHs) are structures usually located close to health facilities able to provide emergency obstetric care. Women can decide to be hosted in MWHs and when labour begins they move to the health facility for the delivery. Although the effectiveness of MWHs is debated, literature shows increasing findings about their importance. Aim of the study is to describe a one-year activity of a MWH located in Angola. Methods: Since 2000, Italian Non-Governmental Organization (NGO) Doctors with Africa CUAMM supports the activities of the hospital of Chiulo in the district of Ombadja (Cunene province). Among the implemented projects, the NGO supports the local MWH (in Portuguese, "casa de espera"), providing dedicated staff and food for all the women hosted in the MWH. The MWH team routinely performs antenatal care visits and brief talks regarding maternal health. In case of pregnancy complications, the staff promptly refers women to the nearby hospital. The MHW team is also involved in routine data collection. Results: In 2018, 703 women were admitted in the MWH. Three-hundred and forty-two (48.6%) were between 18 and 24 years of age. Four-hundred and eighty-two (68.6%) were invited to join the MWH by personnel of local health facilities, while 160 (22.8%) by family members and 61 (8.7%) by community health workers/traditional birth attendants. Age less than 18, previous abortion and/or caesarean were the most assessed factors for high risk pregnancy. In 2018, 1364 deliveries were performed in the hospital, and 593 (43.5%) concerned women hosted in the MWH. Conclusions: To achieve the 2030 Sustainable Development Goals targets regarding maternal and neonatal mortality, the implementation of MHWs could represent an effective tool, especially in countries such as Angola where these indicators show a weak annual reduction. Regarding Chiulo's MWH, an improvement of data collection could lead to a better comprehension of the efficacy of the facility. Key messages: In the SDGs era, countries with a high burden of maternal and neonatal mortality should implement various and integrated approaches to achieve significant reductions of these indicators. Although the effectiveness of maternity waiting homes is still debated, increasing findings suggest that they could represent an effective tool to contain mother and child mortality.